Teletandem within the context of closely-related languages: A Portuguese-spanish interinstitutional experience - De Carvalho, Kelly Cristiane Henschel Pobbe de [UNESP]; Messias, Rozana Aparecida Lopes [UNESP]; Días, Anelly Mendoza (FapUNIFESP (SciELO), 2015)
This paper is part of an ongoing research project aimed at observing the ways that Brazilian undergraduate students who are majoring in Portuguese and Spanish as part of a Foreign Languages and Literatures (FLL) degree program organize and implement the teaching of Portuguese for Spanish speakers within a teletandem context. We sought to evaluate the organization of the content of Portuguese language that they are teaching and the impact made by teletandem practices on the professional development of these student-teachers in both languages. Methodologically, the study is grounded on critical qualitative research. Data analysis suggests that, because Portuguese an d Spanish are closely related languages with a high level of inter-comprehension, the virtual learning context of teletandem requires the presence of a teacher-mediator to conduct the mediation sessions with focused attention to contrasting linguistic and cultural aspects between both languages.
Keywords: Teacher development; Teaching-learning of portuguese/Spanish; Teletandem